An Empirical Analysis of the ASEAN-4's Causality between Exports and Output Growth - Lam, Tri Dung (International Journal of Economics and Financial Issues, 2016)
This paper specifically focuses on analysing the causality between real GDP and real export of goods and services of the ASEAN-4 countries (Indonesia, Malaysia, Thailand and the Philippines) by using comprehensive econometric techniques such as the unit root test, cointegration test, and error correction model. This study reveals that for short-run dynamics, while bi-directional Granger-causality exists in Malaysia, the Philippines, and Thailand; the unidirectional Granger-causality runs from GDP growth to EXP growth for Indonesia. While the long-run relationship shows a bidirectional Granger-causality between GDP and EXP growth for Malaysia and Thailand, GDP growth Granger-caused EXP growth for Indonesia and an inverse relationship exists between these two variables for the Philippines. Keywords: ASEAN-4, Causality, Exports-Output Growth. JEL Classifications: O1, O2, O4, O5